2000
DOI: 10.1023/a:1008136326756
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The haemagglutinin-neuraminidase (HN) gene ofNewcastle disease virus (NDV) strain AF2240, amplifiedfrom the viral genomic RNA ( approximately 1.8 kb) was directionallycloned and inserted into a baculovirus expressionvector system. The recombinant glycoprotein expressedin Spodoptera frugiperda (Sf9) cellsshowed haemagglutinin (HA), neuraminidase (NA) andhemadsorption activities. HA activity was detected inboth extra- and intra-cellular recombinant HN(recHNAF2240) samples. In addition, both HA andhemadsorption a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…In addition, it produced a low expression level of a rHN protein product with a molecular weight of approximately 75 kDa, which corresponded to the glycosylated form of HN protein from the authentic NDV. These findings are in accordance with those of previous studies [30,31,34] and suggest that most of the rHN protein was extracted from infected cells in its unglycosylated form prior to glycosylation [30] or that the glycosylated form of rHN protein was expressed at low levels by the recombinant baculovirus in insect cells. Further study is needed to investigate how such glycosylation affects the antigenic structure of the HN protein; nevertheless, the rHN antigen prepared from insect cells in this study had high HA unit titers, and the HA activity was inhibited in the presence of NDV antibodies, indicating that the rHN protein possessed biological function (such as HA activity) of HN protein from the authentic NDV.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In addition, it produced a low expression level of a rHN protein product with a molecular weight of approximately 75 kDa, which corresponded to the glycosylated form of HN protein from the authentic NDV. These findings are in accordance with those of previous studies [30,31,34] and suggest that most of the rHN protein was extracted from infected cells in its unglycosylated form prior to glycosylation [30] or that the glycosylated form of rHN protein was expressed at low levels by the recombinant baculovirus in insect cells. Further study is needed to investigate how such glycosylation affects the antigenic structure of the HN protein; nevertheless, the rHN antigen prepared from insect cells in this study had high HA unit titers, and the HA activity was inhibited in the presence of NDV antibodies, indicating that the rHN protein possessed biological function (such as HA activity) of HN protein from the authentic NDV.…”
Section: Discussionsupporting
confidence: 93%
“…The rHN antigen had a high yield of HN protein with 2 13 HA units per 25 µL, which matched the inactivated NDV antigen prepared using the same volume of allantoic fluid from chicken eggs. Ong et al [31] reported that the rHN protein produced from recombinant virus-infected cell lysates had HA titers of 2 4 HA units. The rHN protein yield reported by Ong et al [31] was very low when compared with that in this study, which was probably due to differences in the virus strain used for expression of the rHN protein gene, the baculovirus expression system, or the procedure for rHN protein extraction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, gH expressed in mammalian cells requires other HSV-1 factors to be translocated to the cell surface, whereas in insect cells expression of gH alone was sufficient for transport (Ghiasi et al, 1991). The insect cell surface-display of the haemagglutininneuraminidase (HN) glycoprotein of Newcastle disease virus (NDV) resulted in hemadsorption, hemagglutination, and neuraminidase activities (Niikura et al, 1991;Murakami et al, 1994;Ong et al, 2000). Insect cells displaying HN have been deployed as immunogens to inoculate chickens and provided protection against NDV (Niikura et al, 1991).…”
Section: Display Of Infectious Viral Proteinmentioning
confidence: 99%
“…Ong and colleagues have successfully expressed recombinant HN in S. frugiperda cells. Their study showed that the recombinant HN exhibits haemagglutination and neuraminidase activities (Ong et al, 2000). In another study, Choi and colleagues expressed recombinant HN in Sf9 cells, the rHN protein expressed from infected cells was used as an antigen in a hemagglutination inhibition (HI) test for the detection and titration of NDV-specific antibodies present in chicken sera.…”
Section: Introductionmentioning
confidence: 99%